Commissions (Edition 2016) (OECD Insurance Statistics, 2016)
This dataset includes statistics related to commissions in the reporting country, containing a breakdown between domestic companies, foreign-controlled companies and branches and agencies of foreign companies. The commissions in the reporting country can then be compared by ownership (domestic undertakings, foreign controlled undertakings, branches and agencies of foreign undertakings), by insurance type ( life, non-life, composite) and facultative reinsurance(direct business, reinsurance accepted). Data are expressed in national currency, USD or Euro (in millions) and presented from 1993 onwards